Aortic valve replacement via mini-sternotomy: Results of a single centre analysis (UCC Student Medical Journal, 2024)
Background: The traditional method of Aortic Valve Replacement (AVR) is via full sternotomy. However, this incision may not heal properly and cause significant pain. Minimally-invasive approaches have been adopted, including mini-sternotomy. These have gained popularity due to smaller incision, reducing surgical trauma. The hypothesis is that AVR via mini-sternotomy is a safe alternative to full sternotomy. The objective was to analyse and describe results of patients who underwent the procedure, including post-operative outcomes.Methods: A retrospective database review was performed on patients who underwent AVR via mini-sternotomy between September 2016 and December 2022 in Cork University Hospital (CUH). Exclusion criteria included patients who had an aortic procedure concurrently, such as ascending aorta replacement, and those under 18 years. Results for variables, such as age, were expressed as a mean.Results: 93 patients were included; the average age was 68. Average bypass and cross-clamp times were 92 and 73 minutes respectively. Median post-operative length of stay was 8 days and median ICU length of stay was 3 days. There were no in-hospital mortalities.Conclusion: AVR via mini-sternotomy has cosmetic advantages and is particularly useful in frail patients who may suffer from a conventional sternotomy and associated morbidities. It is shown to be a safe alternative with comparable intra- and post-operative outcomes to those described internationally.
Keywords: Aortic valve replacement; Mini-sternotomy; Post-operative outcomes; Aortic valve replacement via mini-sternotomy